STRATEGI GURU PENDIDIKAN AGAMA ISLAM DALAM MENGAJARKAN FARDHU KIFAYAH DI MADRASAH ALIYAH SWASTA ALMANAR HAMPARAN PERAK - Halamsyah Hamdani; Sokon Saragih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the strategies of Islamic Religious Education (IRE) teachers in teaching fardhu kifayah at Madrasah Aliyah Swasta (MAS) Al Manar Hamparan Perak. The subject of fardhu kifayah is crucial in fostering religious awareness, social responsibility, and the implementation of Islamic values in community life. This research employs a descriptive qualitative approach, with data collected through observations, in-depth interviews with IRE teachers and students, as well as documentation related to the learning process. The data were analyzed using Miles and Huberman’s interactive model, which includes data reduction, data display, and conclusion drawing.The results show that the IRE teacher strategies in MAS Al Manar Hamparan Perak include: (1) contextual learning strategies, by linking fardhu kifayah materials with students’ social realities; (2) direct practicum strategies, such as simulating funeral rites, to strengthen practical skills; (3) collaborative strategies, through group work and discussions to cultivate collective responsibility; and (4) habituation strategies, by assigning practical tasks outside the classroom so students can internalize fardhu kifayah values in real life. The discussion emphasizes that the success of teacher strategies is determined by creativity, the use of approaches that suit students’ characteristics, and support from the school environment. The implication of this study is the need for developing Islamic Religious Education strategies based on real-life practice, so that students not only understand fardhu kifayah theoretically but are also able to implement it in their social life.